2009
DOI: 10.1007/s00702-009-0345-3
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional evaluation of cognitive functioning in children, adolescents and young adults with ADHD

Abstract: Attention-deficit/hyperactivity disorder (ADHD) often persists into adulthood, albeit with changes in clinical symptoms throughout the life span. Although effect sizes of neuropsychological deficits in ADHD are well established, developmental approaches have rarely been explored and little is yet known about age-dependent changes in cognitive dysfunction from childhood to adulthood. In this cross-sectional study, 20 male children (8-12 years), 20 adolescents (13-16 years), and 20 adults (18-40 years) with ADHD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
55
2
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 82 publications
8
55
2
2
Order By: Relevance
“…But when children and adults were analyzed separately, only children presented the underreproduction of longer time duration compared to controls. Contrary to previous studies, 14,15) our results which showed no correlation between accuracy of time reproduction and aging can be explained as follows: we confined participants to children and adolescents, whereas the previous two studies 14,15) had included adults. Because of the absence of the adult group in our sample, our results may not reflect a more definite age effect and developmental trajectory continuing into adulthood was not observed in ADHD population.…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations
“…But when children and adults were analyzed separately, only children presented the underreproduction of longer time duration compared to controls. Contrary to previous studies, 14,15) our results which showed no correlation between accuracy of time reproduction and aging can be explained as follows: we confined participants to children and adolescents, whereas the previous two studies 14,15) had included adults. Because of the absence of the adult group in our sample, our results may not reflect a more definite age effect and developmental trajectory continuing into adulthood was not observed in ADHD population.…”
Section: Discussioncontrasting
confidence: 53%
“…Marx et al 14) found a general time reproduction deficit in 20 children, 20 adolescents, and 20 adults with ADHD. However, time reproduction error tended to decline with increasing age in ADHD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…however abnormalities persisted into adulthood in individuals with ADHD compared to controls (Marx et al, 2010).…”
Section: Introductionmentioning
confidence: 99%